2012
DOI: 10.1353/hpu.2012.0148
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic Differences in Fears and Mistrust Contributing to Unwillingness to Participate in Cancer Screenings

Abstract: Effective provider-patient relationships are vital for positive patient health outcomes. This analysis assessed sociodemographic differences in fears and mistrust related to the provider-patient relationship, which may contribute to unwillingness to participate in cancer screenings (CSs). The data are from a stratified, random-digit dial telephone questionnaire of non-institutionalized households in New York, Maryland, and Puerto Rico. Statistically significant results indicate that Hispanics, compared with Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 33 publications
1
44
1
Order By: Relevance
“…As might be expected, patients diagnosed with colorectal cancer after a negative screening result reported lower trust in the results of FOBt screening, and this is potentially a cause for concern. Medical mistrust has been associated with reduced willingness to undergo cancer screening, particularly among ethnic minority groups and people with lower socioeconomic status (31)(32)(33). These studies assessed trust in "medical people" among members of the public, the majority of whom would not have had cancer.…”
Section: Discussionmentioning
confidence: 99%
“…As might be expected, patients diagnosed with colorectal cancer after a negative screening result reported lower trust in the results of FOBt screening, and this is potentially a cause for concern. Medical mistrust has been associated with reduced willingness to undergo cancer screening, particularly among ethnic minority groups and people with lower socioeconomic status (31)(32)(33). These studies assessed trust in "medical people" among members of the public, the majority of whom would not have had cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the noted perception among focus group participants included medical mistrust due to lack of respect from medical professionals. This could be contributed to sociodemographic factors such as socioeconomic status, educational attainment, and health literacy (Davis, Bynum, Katz, Buchanan, & Green, 2012). For example, the perception that medical practitioners do not want to touch the participants may be a derivative of personal and cultural preconceptions about how people of color with low social class status address personal hygiene or other health-related care.…”
Section: Discussionmentioning
confidence: 99%
“…Another study that collected data using a stratified, randomdigit dial telephone questionnaire of noninstitutionalized households in New York, Maryland, and Puerto Rico, reported that compared with whites, Latinos were nearly two times more likely to report that fear of being a 'guinea pig' and lacking trust in medical people made them unwilling to participate in cancer screening (Davis et al, 2012).…”
Section: Cultural Mistrust: An Added Burden For Nondominant Populationsmentioning
confidence: 99%